Detection of spatial frequency in brain-damaged patients: influence of hemispheric asymmetries and hemineglect - Dos Santos, Natanael A.; Andrade, Suellen M.; Calvo, Bernardino F. (Frontiers in Human Neuroscience, 2013)
Hemispheric specialization for spatial frequency processing was investigated by measuring the contrast sensitivity curves of sine-wave gratings in 30 left or right brain-damaged patients using different spatial frequencies compared with healthy participants. The results showed that left brain-damaged patients were selectively impaired in processing high frequencies, whereas right brain-damaged patients were more impaired in the processing low frequencies, regardless of the presence of visuo-spatial neglect. These visual processing results can be interpreted in terms of spatial frequency discrimination, with both hemispheres participating in this process in different ways.